DQB1*06:02-Associated Pathogenic Anti-Myelin Autoimmunity in Multiple Sclerosis-Like Disease: Potential Function of DQB1*06:02 as a Disease-Predisposing Allele - Kaushansky, Nathali; Ben-Nun, Avraham (Frontiers in Oncology, 2014)
Susceptibility to Multiple Sclerosis (MS) has been linked mainly to the HLA-DRB1 locus, with the HLA-DR15 haplotype (DRB1*1501-DQA1*0102-DQB1*0602- DRB5*0101) dominating MS-risk in Caucasians. Although genes in the HLA-II region, particularly DRB1*1501, DQA1*0102-DQB1*0602, are in tight linkage disequilibrium (LD), genome-wide-association and gene candidate studies identified the DRB1*15:01 allele as the primary risk factor in MS. Many genetic and immune-functional studies have indicated DRB1*15:01 as a primary risk factor in MS, while only some functional studies suggested a disease-modifying role for the DRB5*01 or DQB1*06 alleles. In this respect, the susceptibility of DRB1*15:01- transgenic (Tg) mice to MBP- or MOG-induced MS-like disease is consistent with primary contribution of DRB1*15:01 to HLA-DR15+ MS. The studies summarized here show that susceptibility to MS-like disease, induced in HLA-“ humanized” mice by MOBP or by the PLP, one of the most prominent encephalitogenic target-antigens implicated in human MS, is determined by DQB1*06:02, rather than by the DRB1*15:01 allele. These findings not only offer a rationale for a potential role for DQB1*06:02 in predisposing susceptibility to MS, but also suggest a more complex and differential functional role for HLA-DR15 alleles, depending on the primary target myelin antigen. However, the conflict between these findings in HLA-Tg mice and the extensive genome-wide-association studies (GWASs) which could not detect any significant effect from the DQB1*06:02 allele on MS risk is rather puzzling. Functional analysis of MS PBLs for DQB1*06:02-associated anti-myelin autoimmunity may resolve whether or not the DQB1*06:02 is associated with MS pathogenesis.